Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada Restoran Waralaba Asing di Kota Denpasar - Suryawarman, A.A.Ngurah Kameswara; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 2 No 1 (2013), 2012)
Reliable accounting information systems is indispensable by the foreign franchise restaurants to increase service to consumers and also produce more accurate information. Sampling of this research is saturate sample method. Respondents of this research are 78 employees who working in a foreign franchise restaurants and registered as a taxpayer hotels and restaurants in Denpasar Revenue Service in 2012 which working using an accounting information system. Multiple linear regression analysis techniques provide results that variable t echnical c apability of a ccounting i nformation sy stem p ersonal , management support, user training and education programs, the quality of information and the use of software within organization partially significant on the performance of accounting information systems as measured by user satisfaction. Variable user involvement in the development process, organization size and formalisation of accounting information system development did not partially significant on the performance of accounting information systems as measured by user satisfaction. Keywords : u ser i nvolvement in the d evelopment process , t echnical c apability of a ccounting i nformation sy stem p ersonal , o rganization s ize , m anagement s upport , f ormalisation of accounting i nformation s ystem d evelopment , u ser t raining and e ducation p rogram, the quality of information and the use of software within organization
Keywords: id